Measuring Factor Affecting Indonesia’s Seafarers Retention - Christopher Samosir; Anita Maharani; Muchlis Burhanuddin (Journal of Business and Management Review, 2021)
The purpose of this study was to determine the extent to which human resource management contributes to employee retention. This study refers to concepts related to human resource management and several studies that show the factors influenced by employee retention. This research approach is quantitative, with the research subjects are employees who work in the sea crossing business. Based on the research results on marine employees of the company, the managerial implications intended for companies engaged in sea crossing services are that there is an influence of placement, compensation, and corporate culture variables on employee retention, which has a positive and significant effect. From the research results, corporate culture is not a moderator of placement and compensation variables on retention, so companies need to re-assure other variables that strongly influence the weak relationship between variables that can increase employee retention.